Twelve-Week Quadriceps Strength as A Predictor of Quadriceps Strength At Time Of Return To Sport Testing Following Bone-Patellar Tendon-Bone Autograft Anterior Cruciate Ligament Reconstruction - Joseph P Hannon; Sharon Wang-Price; Shiho Goto; Steven Singleton; Lindsey Dietrich; James Bothwell; Curtis Bush; Craig Garrison (International Journal of Sports Physical Therapy)
# Background